Naik Dango Tradition in Supporting Social Integration of Ethnic Dayak Community Kanayatn Binua Sunge Samak Kubu Raya Regency, West Kalimantan - Bahri, Saiful; Lestari, Emi Tipuk (Komunitas, 2022)
The purpose of this study is to analyze the tradition of naik dango in supporting the social integration of the  Kanayatn Dayak ethnic community in Binua Sunge Samak, Sungai Ambawang District,  Kubu Raya Regency. The Naik Dango tradition is one of the rituals carried out by the Kanayatn Dayak people as an expression of gratitude to Jubata (God) who has given abundant results for their efforts. This research uses a qualitative approach with ethnographic methods.  Data are obtained through participation observations, interviews with informants and documentation. The result of this research is that the tradition of naik dango marks the end of the farming process, celebrated as a form of joy, friendship as well as an expression of gratitude to (Jubata) the Creator for the rice yields obtained.  The tradition of naik dango can support the creation of normative social integration in the form of obedience and obedience in preserving the values and norms that exist in the tradition of naik dango.